Creating a University Strategic Plan to Address Relationship Violence and Sexual Misconduct (RVSM): An Application of Principles-Focused Evaluation at Michigan State University. (January 2023) - Campbell, Rebecca; Munford, Andrea; Moylan, Carrie A.; PettyJohn, Morgan E.; Schweda, Kelly; Fedewa, Tana; Rosen, Holly; Ferguson, Mary Ann; Beal, Jesse; Buchanan, NiCole T.
This paper describes a multi-year initiative at Michigan State University (MSU) to change our institutional response to relationship violence and sexual misconduct (RVSM) in the aftermath of a large-scale institutional crisis. While the circumstances at MSU are unique, many universities have faced or will face moments that bring RVSM issues into the spotlight. To inform other colleges and universities, we describe how we developed a 5-year strategic plan to transform services for survivors and develop prevention programming for multiple audiences and at multiple levels of analysis. We titled this framework Know More. Do More. Support More, w hereby "know more" reflects our ongoing use of campus climate surveys and data sharing to educate our community about RVSM; "do more" includes our institutional-level strategic plan for culture change; and "support more" provides guidance to our community members on how to respond to disclosures in a trauma-informed way and connect survivors to support services. We discuss the challenges and opportunities that stemmed from our choice to work "within the system" to create this model, as well as the ethical dilemmas we faced in these partnerships.